Penerapan Terapi Aktivitas Berjalan Kaki untuk Mengurangi Sakit Kepala pada Penderita Hipertensi - Taufaila Rifqah, Farisa; Freeska Dwi Marta, Ollyvia (Jurnal Pustaka Keperawatan (Pusat Akses kajian Keperawatan), 2025)
Hypertension is a major non-communicable disease often referred to as a silent killer due to its asymptomatic nature and potential to cause serious complications. Walking exercise is one of the recommended non-pharmacological interventions proven to help reduce blood pressure. This case study, using a nursing care approach, aims to examine the effect of walking therapy on lowering blood pressure and reducing headache intensity in a 62-year-old female patient living in Pakis Village, Malang Regency. The intervention consisted of a 30-minute daily walking session for seven consecutive days. The results showed a decrease in blood pressure from 160/95 mmHg to 140/85 mmHg, along with a reduction in headache intensity from a score of 6 (moderate pain) to 2 (mild pain). Physiologically, walking improves vascular elasticity, reduces stress hormones, and stimulates the release of endorphins that act as natural analgesics. These findings indicate that walking therapy is an effective, safe, and practical non-pharmacological nursing intervention to support hypertension management and improve the quality of life in older adults.